Impact of COVID-19 on rural women and men in Cross River and Kaduna states, Nigeria - Gupta, Shweta; Alvi, Muzna; Ringler, Claudia (2021)
Prepared by Shweta Gupta, Muzna Alvi and Claudia Ringler Data collected by Finmark